REVITALIZING INDIGENOUS AGRICULTURAL KNOWLEDGE AND PRACTICES: MANUGAL AS AN ENVIRONMENTALLY SUSTAINABLE FARMING METHOD IN DAYAK NGAJU, INDONESIA - Elly Diah Praptanti; Alfian, Andi (Universitas 17 Agustus 1945 Semarang, 2023)
For thousands of years, the Dayak Ngaju people in Central Kalimantan have practiced a traditional rice cultivation system called Manugal, which involves planting rice directly on the ground without artificial fertilizers or pesticides. This method relies on rainwater and natural materials, and it is guided by the teachings of the Kaharingan belief system, recognizing rice as a divine manifestation, and adhering to the traditional calendar. However, the Green Revolution and the globalization of modern food production, initiated in the late 1960s, introduced intensive agriculture, chemical inputs, and high-yielding crop varieties. This modernization marginalized local traditions, including Manugal, in Central Kalimantan. This qualitative descriptive case study examines the background of the Green Revolution and its impact on Manugal, the ecological consequences of agricultural modernization, and the comparison between Manugal and modern monoculture farming systems. The study aims to propose strategies for maintaining the Manugal tradition and achieving ecological sustainability.